2021
DOI: 10.4103/jfmpc.jfmpc_1528_20
|View full text |Cite
|
Sign up to set email alerts
|

Role of platelet count and mean platelet volume and red cell distribution width in the prediction of preeclampsia in early pregnancy

Abstract: Introduction: Mean platelet volume (MPV), platelet count (PC), and red cell distribution width (RDW) are various blood indices that play important role in preeclampsia. This study aimed to evaluate the role of MPV, RDW, and PC for the prediction of preeclampsia in the early second trimester of pregnancy and to observe its correlation with disease severity. Material and Methods: A prospective case-control study was conducted for 1 year in the Department of Obstetrics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 24 publications
2
11
0
1
Order By: Relevance
“…This leads to increased platelet turnover and can result in the higher immature platelet fraction (IPF) with increased mean platelet volume (MPV) that accompanies the thrombocytopenia in healthy pregnancies. However, pathologic exacerbation of this innate platelet activation in GH and PE may account for the higher MPV and IPF seen in our small cohort, and as reported by others [53,62,63].…”
Section: Discussionsupporting
confidence: 79%
“…This leads to increased platelet turnover and can result in the higher immature platelet fraction (IPF) with increased mean platelet volume (MPV) that accompanies the thrombocytopenia in healthy pregnancies. However, pathologic exacerbation of this innate platelet activation in GH and PE may account for the higher MPV and IPF seen in our small cohort, and as reported by others [53,62,63].…”
Section: Discussionsupporting
confidence: 79%
“…As well, Sachan et al [16], reported that neutrophil was significantly high in Severe PE group in comparison to the mild group. However, there was no statistically significant difference between the two preeclampsia groups as regard Hemoglobin, Lymphocyte, platelets, MPV and RDW.…”
Section: Discussionmentioning
confidence: 75%
“…NLR showed a non-significance with AUC 0.557 P-value 0.097 at cut-off value 5.05. While Sachan et al [16], reported that the best predictor of PE was MPV with AUC 0.643 and Pvalue 0.002 at a cutoff value of ≥9.05 fl with 50.0% sensitivity and 82.4% specificity. While RDW, at a cut-off value of ≥11.5% had AUC 0.751 and P-value 0.001 with 85.3% sensitivity and 49.0% specificity.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…If PI and MAP are used synergistically with mathematically calculating PE risks using maternal characteristics, it will exhibit a high detection rate of 89% for early-onset PE, but still only 57% for late-onset PE at a FPR of 10% [ 18 ]. Since PE-induced pulmonary embolism commonly causes increased levels of mean platelet volume (MPV) and red cell distribution width (RDW), the blood tests detecting platelet count, mean platelet volume, and red cell distribution width have been raised as significant markers of PE [ 19 , 20 ]. Although hemo-diagnosis possesses several advantages of fast and low-cost, their specificity and sensitivity are still unsatisfactory.…”
Section: Introductionmentioning
confidence: 99%